The Impact of Nonsurgical Periodontal Therapy on the Salivary Proteome: A Pilot Study - Stefania Bergamini; Elisa Bellei; Valentina Selleri; Roberta Salvatori; Giulia Micheloni; Milena Nasi; Marcello Pinti; Carlo Bertoldi (International Journal of Dentistry)
Conclusions: Salivary proteome analysis revealed a distinct disease-associated protein signature in G2 group, supporting its potential as a noninvasive tool for diagnosis and monitoring of Pd patients. The post-NSPT shifts in protein expression further highlight the effectiveness of periodontal therapy in modulating inflammatory biomarkers. Future studies on larger cohorts are needed to validate these findings and advance saliva-based proteomics toward personalized periodontal care.